2022
DOI: 10.3389/fonc.2022.1007236
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics analysis and validation of the critical genes associated with adamantinomatous craniopharyngioma

Abstract: Adamantinomatous craniopharyngioma (ACP) is an epithelial tumor that arises when Rathke’s pouch remains during embryonic development. The pathogenesis of ACP remains unclear, and treatment options are limited. Here, we reveal the critical genes expressed in ACP and provide a basis for further research and treatment. The raw dataset GSE94349 was downloaded from the GEO database. We selected 24 ACP and 27 matched samples from individuals with no documented tumor complications (control group). Then, we screened f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…ECM organisation, Naba matrisome-associated activity, and collagen metabolic processes are all related to the ECM. The ECM can promote cell migration and differentiation and trigger EMT, which is important in the progression and metastasis of various tumours [ 18 ]. EMT also plays a crucial role in ACP development.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ECM organisation, Naba matrisome-associated activity, and collagen metabolic processes are all related to the ECM. The ECM can promote cell migration and differentiation and trigger EMT, which is important in the progression and metastasis of various tumours [ 18 ]. EMT also plays a crucial role in ACP development.…”
Section: Discussionmentioning
confidence: 99%
“…ACP is thought to be driven by mutations in exon 3 of CTNNB1 [ 18 ]. Previous study has shown that β-catenin may regulate the expression of CDH1 in ACP, which is the most critical gene for the occurrence and development of ACP; moreover, its decreased expression has been associated with tumour recurrence [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation